ANALYTICAL MODEL FOR BUCKLING LENGTH COEFFICIENT DETERMINATION IN STEEL TRUSSES: A LATERAL TORSIONAL BUCKLING APPROACH - Dalila Boukhalfa; Toufik Belaid; Adel Slimani; Fatiha AMMARI (International Journal for Computational Civil and Structural Engineering, 2024)
This paper presents a contribution to the study of the stability of steel trusses. The paper proposes an analytical model for the determination of the buckling length coefficient of the truss N by the lateral torsional buckling approach. The model is derived by considering the equilibrium of the truss under the action of the applied loads and the buckling load. The buckling load is determined by considering the lateral buckling of the equivalent beam and the interaction between the members. The model is validated by comparing the predicted buckling loads with the experimental results of several steel trusses. The results show that the model can predict the buckling loads with good accuracy. The proposed model is a valuable tool for the design of steel trusses. The model can be used to determine the buckling length coefficient of the truss and to ensure that the truss is safe and reliable.